Group portrait of the attendees of the YMCA "Friendly Indian Pow Wow" in Millbrae - Gordon, John C., 1887-1967 (photographer):::Creator::::::::::::
Group portrait of mostly young boys, with adult men and women posing for the Y.M.C.A. Friendly Indian Pow-Wow. The adults are seated in the back row. The young boys are wearing paper headbands with feathers. The front of headband bares the title "Y.M.C.A. Friendly Indian Pow-Wow." Some of the boys are holding painted shields, and one boy sitting near the top center of the photograph wears a feather headdress. On the far right, a young boy stands holding the American flag.